“Hazain Pirouit”: Nikos Kazantzakis from Odysseia to Inside the Knossos’ Palaces: Educational Transformations - Παπαδογιαννάκης Νικόλαος Ε. (Education Sciences, 2019)
Kazantzakis worked for 15 years to finish his main work Odysseia and now wants to rest, to relax … In this paper we are trying to compare the Rapsodies E, Z, Θ of Odysseia, representing the Minoan civilisation with some events of the novel for children In Knossos' Palaces. Of course, the pictures in the novel are not very strong, because it is meant for young readers. In both works the subject refers to the colupse of a Civilization and the forces that accelarate the colupse and organize the new situation... Kazantzakis has lived the horror of the First World War and its results. He is influenced by the War and this is obvious in both works.